The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1111/j.1469-7610.2012.02564.x
|View full text |Cite
|
Sign up to set email alerts
|

Preterm infants who are prone to distress: differential effects of parenting on 36‐month behavioral and cognitive outcomes

Abstract: Background The differential susceptibility (DS) model suggests that temperamentally prone-to-distress infants may exhibit adverse outcomes in negative environments but optimal outcomes in positive environments. This study explored temperament, parenting, and 36-month cognition and behavior in preterm infants using the DS model. We hypothesized that temperamentally prone to distress preterm infants would exhibit more optimal cognition and fewer behavior problems when early parenting was positive; and less optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 47 publications
(52 reference statements)
7
64
1
1
Order By: Relevance
“…In some studies, temperament is associated with IEP, but it can also be a moderator between other risks (e.g., contextual, maternal) and IEP (c.f. Poehlmann et al 2012). This is consistent with Belsky's (1997) differential susceptibility hypothesis, which argues that the environment affects children differently depending on their temperament.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In some studies, temperament is associated with IEP, but it can also be a moderator between other risks (e.g., contextual, maternal) and IEP (c.f. Poehlmann et al 2012). This is consistent with Belsky's (1997) differential susceptibility hypothesis, which argues that the environment affects children differently depending on their temperament.…”
Section: Discussionsupporting
confidence: 88%
“…One study (Poehlmann et al 2012) indicated that intrusive and frustrated interactions between parents and children do not increase IEP, but the same study reported that low developmental stimulation (Poehlmann et al 2012) is associated with IEP. Other studies stated that low emotional stimulation (Twomey et al 2013) and less sensitive parenting (Ciciolla et al 2014) increase the odds of children developing IEP.…”
Section: Disciplinary Practices/parental Interactionmentioning
confidence: 94%
“…Early mother-infant interactions following term birth are critical factors in child development (Forcada-Guex et al 2011;Hofer 1994;Meijssen et al 2011) and are of great relevance for premature infants due to their increased vulnerability to cognitive, socio-emotional, and behavioral difficulties (Feeley et al 2005;Landry et al 2003). Enhanced sensitivity and responsiveness between mothers and preterm infants can lead to better long-term outcomes in cognitive and social development (Feeley et al 2005;McManus and Poehlmann 2012;Poehlmann et al 2012). Work by others suggests that promoting more optimal parent-infant interactions through an educational and behavioral intervention may lead to reductions in post-discharge maternal depression and anxiety (Melnyk et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…The findings revealed that the risk for poor intellectual performance was increased more for the children of the smoking mothers than the non-smoking mothers. Similarly, Poehlmann et al (2012) reported that early exposure of pregnant women to stress caused more critical parenting, and this consequently caused externalizing problems at 9 months. In the same fashion, Evans et al (2011) also reported pre-birth period as an important time frame for maternal depression and its effect on children's cognitive developments.…”
Section: Parental Educationmentioning
confidence: 99%